LABORATORY PARAMETERS OF CHRONIC OSTEOMYELITIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chronic osteomyelitis (CS) is a long-term infectious and inflammatory disease of bone tissue, often complicated by the formation of sequestration and purulent fistulas. Diagnosis of CS is difficult due to the nonspecific clinical manifestations and the need to differentiate with other pathologies of the bone system. Laboratory parameters play an important role in confirming the diagnosis, assessing the activity of the inflammatory process and monitoring the effectiveness of treatment. This article discusses the key laboratory markers used in the diagnosis and monitoring of CS. These include indicators of a general blood test (leukocytosis, a shift in the leukocyte formula to the left, an increase in ESR), biochemical parameters (C-reactive protein, procalcitonin), as well as microbiological studies (seeding of purulent discharge on bacterial flora and determination of sensitivity to antibiotics).